Applications of Advanced MRI to Disorders of Consciousness - Fischer, David; Newcombe, Virginia; Fernandez-Espejo, Davinia; Snider, Samuel B. (Seminars in Neurology, 2022)
Disorder of consciousness (DoC) after severe brain injury presents numerous challenges to clinicians, as the diagnosis, prognosis, and management are often uncertain. Magnetic resonance imaging (MRI) has long been used to evaluate brain structure in patients with DoC. More recently, advances in MRI technology have permitted more detailed investigations of the brain's structural integrity (via diffusion MRI) and function (via functional MRI). A growing literature has begun to show that these advanced forms of MRI may improve our understanding of DoC pathophysiology, facilitate the identification of patient consciousness, and improve the accuracy of clinical prognostication. Here we review the emerging evidence for the application of advanced MRI for patients with DoC.
Keywords: neuroimaging; MRI; disorders of consciousness; prognostication